CLUSTER FORMATION OF ZOOPLANKTON AND ITS RELATION TO SEASONAL VARIATION - MARUTHANAYAGAM, C.; SUBRAMANIAN, P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The survey of zooplankton was carried out in Plak Bay near to Mandapam. Regular fortnightly sample collections were made for two years from November 1993 to October 1995. A total of 81 species of zooplankton were observed during the study period. The abundance and distribution pattern of each and every species show direct relation to seasonal effect. The results also affirm significant cluster formation during the study period.